PENGEMBANGAN PANDUAN PRAKTIKUM GENERATOR SATU FASE DAN TIGA FASE BERBASIS INKUIRI TERBIMBING DENGAN MENTORING - Tulandi, Djeli Alvi; Marianus, Marianus; Yohan, Jibrael (Universitas Negeri Manado, 2020)
This research is motivated by the absence of practicum guides for one-phase and three-phase generator tools so that students lack expertise in using these tools in experimenting. The purpose of this study is to produce a physics practicum guidance product on a one-phase and three-phase generator using a guided inquiry model with mentoring. This research is a research and development study using the 4D research model adapted from the Thiagarajan model, which is define, design, develop and disseminate. The results of the study for mentors and groups get an average value of 86.45%, so that the guidelines fall into the feasible / valid category. and on the response of mentors and students 47.17% chose very useful (SB), 51.43% chose useful (B) and 1.4% chose less useful (KB) none voted unhelpful (TB). Based on the results of the study it can be concluded that a product has been produced in the form of a basic physics practicum guide for one-phase and three-phase generator tools using a guided inquiry learning model with good and proper qualifications.Â Keywords: Practicum guide, Research and Development, one-phase and three-phase generators, guided inquiry, mentoring.